The Rotunda at Konjuh: Some Aspects of the Religious and Cultural Policy Influence in Early Cristian Dardania - Obraztsova, Ksenia B. (Actual Problems of Theory and History of Art, 2022)
The article is dedicated to the issues of liturgical arrangement of the Early Christian churches in Eastern Illyricum and, particularly, in Dardania. It is mainly based on a historiographical controversy aiming to attach Illyricum either to the Western, or to the Eastern liturgical practice by means of historical as well as architectural arguments. As a Latin-speaking province, Dardania is of special interest here. According to some evidence actively involved in the current historiography, the province belonged to the Roman sphere of influence and was opposed to the neighbouring Greek-speaking territories. The rotunda at Konjuh was chosen as a descriptive illustration for the problem under consideration. The elements examined in the paper such as the rooms flanking the narthex, eastern compartments, barriers within the colonnade, the synthronon, altar screen, and ambo, were compared with the possible analogues in the Western, Constantinopolitan, and Northern-Greek traditions. As the result, no distinct traces of the Roman influence were revealed; at the same time, Dardania proved to be secularly integrated within the Northern-Greek tradition of church building. This work is supported by the Russian Science Foundation (grant 20-18-00294) and performed in Scientific Research Institute of Theory and History of Architecture and Urban Planning, branch of the Central Institute for Research and Design of the Ministry of Construction and Housing and Communal Services of the Russian Federation.